Recycling Bodhisattva: The Tzu-Chi movement's response to global climate change. (September 2015) - Lee, Chengpang; Han, Ling
This article traces the emergence of climate change discourse and its related practices in one of the largest and globally most influential Taiwanese Buddhist organizations – Tzu-Chi (Buddhist Compassion Relief Tzu-Chi Association). The authors analyse more than 500 volumes of Tzu-Chi's periodicals and describe its recycling practice from the social organizational perspective. Our findings suggest that climate change discourse has emerged in recent years as a response to increasing natural disasters, particularly typhoons. Practices such as recycling are implemented in order to address this crisis through the cultivation of a disciplined inner self. The article compensates for the lack of current studies on what Buddhist organizations actually do for the environment and how they address climate change. It also offers a correction to the studies on environmental movements, in which religious environmentalism is often overlooked.